Early buddhist art of China and Central Asia, volume one : Later Han, Three Kingdoms and Western Chin in China and Bactria to Shan-shan in Central Asia. - Rhie, Marylin Martin. (Leiden)
1.c. (xxxvii, 466 s., 16 res., [401] s.)